A Multilevel Study of Melon Fruit Reticulation Provides Insight into Skin Ligno-Suberization Hallmarks. Issue 4 (30th January 2019) - Cohen, Hagai; Dong, Yonghui; Szymanski, Jedrzej; Lashbrooke, Justin; Meir, Sagit; Almekias-Siegl, Efrat; Zeisler-Diehl, Viktoria Valeska; Schreiber, Lukas; Aharoni, Asaph
Abstract : Ligno-suberization processes in the course of fruit development lead to skin reticulation in melon. Abstract: The skin of fleshy fruit is typically covered by a thick cuticle. Some fruit species develop different forms of layers directly above their skin. Reticulation, for example, is a specialized suberin-based coating that ornaments some commercially important melon ( Cucumis melo ) fruit and is an important quality trait. Despite its importance, the structural, molecular, and biochemical features associated with reticulation are not fully understood. Here, we performed a multilevel investigation of structural attributes, chemical composition, and gene expression profiles on a set of reticulated and smooth skin melons. High-resolution microscopy, surface profiling, and histochemical staining assays show that reticulation comprises cells with heavily suberized walls accumulating large amounts of typical suberin monomers, as well as lignified cells localized underneath the specialized suberized cell layer. Reticulated skin was characterized by induced expression of biosynthetic genes acting in the core phenylpropanoid, suberin, lignin, and lignan pathways. Transcripts of genes associated with lipid polymer assembly, cell wall organization, and loosening were highly enriched in reticulated skin tissue. These signatures were exclusive to reticulated structures and absent in both the smooth surfaces observed in between reticulated regions and in the skin of smooth fruit. Our data provide important insights into the molecular and metabolic bases of reticulation and its tight association with skin ligno-suberization during melon fruit development. Moreover, these insights are likely to contribute to melon breeding programs aimed at improving postharvest qualities associated with fleshy fruit surface layers.